A gender-specific association of the polymorphism Ile197Met in the kininogen 1 gene with plasma irbesartan concentrations in Chinese patients with essential hypertension. (November 2018) - Hu, Shengnan; Cheng, Jun; Weinstock, Justin; Fan, Xiu; Venners, Scott; Hsu, Yi-Hsiang; Suwen Wu,; Pan, Faming; Zha, Xiangdong; Sun, Jinlu; Jiang, Shanqun; Xu, Xiping
Abstract This study was conducted to explore interactions in the association of thekininogen (KNG1) Ile197Met polymorphism and gender with plasma concentrations of irbesartan in Chinese patients with essential hypertension. A total of 1100 subjects with essential hypertension received a daily oral dose of 150 mg irbesartan for twenty-eight consecutive days. High-performance liquid chromatography-fluorescence (HPLC) was used to detect plasma irbesartan concentrations on day 28. TheKNG1 Ile197Met gene polymorphism was determined using high-throughput TaqMan technology. The frequency distribution ofKNG1 Ile197Met genotype conformed to the Hardy-Weinberg equilibrium. After 28 days of treatment, patients with the GG genotype had significantly lower irbesartan concentrations (P  = 0.033) compared to homozygous TT genotype carriers. After stratifying by gender, male G allele carriers had significantly lower irbesartan concentrations (GG, P  = 0.015; TG, P  = 0.015, respectively) relative to TT genotype after adjusting for age, region, body mass index (BMI), smoking, and alcohol consumption. However, there was no significant difference in female subjects. A further test for a multiplicative interaction between theKNG1 Ile197Met polymorphism and gender in association with ln-plasma irbesartan concentrations in a multiple linear regression model was also significant (P for interaction = 0.033). This is the first study to suggest that gender may influence the association of theIle197Met variant ofKNG1 with ln-plasma irbesartan concentration. This finding may indicate that the interaction of gender and theKNG1 Ile197Met gene polymorphism can influence plasma trough irbesartan concentrations, which may contribute to a better development of personalized hypertensive treatment in Chinese patients.